Resisting Gnostic Spiritualism in the Catholic Social Teaching Classroom - Joyce A. Bautch (Journal of Moral Theology, 2022)
In this article I consider what Pope Francis's 2015 special criticism for "any form of gnostic spiritualism" may mean for educating college students about Catholic social teaching. The argument unfolds in two parts. I begin by offering a framework for my ideas. This part consists of my teaching situation and teaching philosophy. In the second part of the article I invite the reader to consider some of my teaching insights and tactics. Before the article ends, I share two learning exercises I employ to develop deeper understanding of compassion and solidarity.